A Novel Mechanism of Cannabidiol in Suppressing Hepatocellular Carcinoma by Inducing GSDME Dependent Pyroptosis - Shangguan, Fugen; Zhou, Hongfei; Ma, Nengfang; Wu, Shanshan; Huang, Huimin; Jin, Guihua; Wu, Shijia; Hong, Weilong; Zhuang, Weiwei; Xia, Hongping; Lan, Linhua (Frontiers in Cell and Developmental Biology, 2021)
Cannabidiol (CBD), a phytochemical derived from Cannabis sativa L., has been demonstrated to exhibit promising anti-tumor properties in multiple cancer types. However, the effects of CBD on Hepatocellular carcinoma cells (HCC) remains unknown. We have shown that CBD effectively suppresses HCC cell growth in vivo and in vitro, and induced HCC cell pyroptosis in a caspase-3/GSDME-dependent manner. We further demonstrated that accumulation of Integrity Stress Response (ISR) and mitochondrial stress may contribute to the initiation of pyroptotic signaling by CBD. Simultaneously, CBD can repress aerobic glycolysis through modulation of the ATF4-IGFBP1-Akt axis, due to the depletion of ATP and crucial intermediate metabolites. Collectively, these observations indicate that CBD could be considered as a potential compound for HCC therapy.